Nonsurgical Orthodontic Treatment of a Severe Open Bite Case Using Miniscrews with Modified Multiloop Edgewise Arch Wire Technique - Abdulkarim A. Hatrom; Bushra Kanwal; Fatima Hamooda; Hashim A. Alzahrani (Case Reports in Dentistry)
Skeletal open bite is one of the most challenging malocclusions to treat and maintain due to the difficulty and instability of correction. Although a combination of orthodontic treatment and orthognathic surgery may be the ideal approach in most cases, the complications, risks, and costs of surgery have sparked an interest in alternative treatment options that use temporary anchorage devices to achieve orthognathic-like effects. Adult patients can be treated without the need for special compliance using temporary anchorage devices such as miniscrews. This case report demonstrates a goal-oriented strategy for nonsurgical treatment of a complex skeletal open bite malocclusion in an adult patient using miniscrews and a modified multiloop edgewise arch wire (MEAW) technique, with the results evaluated clinically and cephalometrically.